2021
DOI: 10.1155/2021/5595235
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Demographical and Lifestyle Factors and Traditional Chinese Medicine Constitution among Macau Elderly Individuals

Abstract: Objectives. To measure the distributed characteristics of Traditional Chinese Medicine (TCM) constitutions, as well as related factors with biased TCM constitutions among the elderly individuals in Macau. Methods. The elderly individuals from elderly healthcare centers located in Macao Peninsula, Taipa, and Coloane were selected as research samples. The basic information questionnaire and the Constitution in Chinese Medicine Questionnaire (CCMQ) for elderly were employed. Descriptive analysis was applied to il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…31,51,52 In addition, our study also found that personal health behavior and dietary characteristics influenced the imbalance of TCM body constitutions. 53–55 It was also worth noting that our study found that drug allergy, depression, somatic comorbidities, and nutritional characteristics of patients with IBS were significantly different from those of subjects with non-IBS in the Gentleness constitution. It was reasonable to speculate that the BCQ in TWB is a cumulative score calculation.…”
Section: Discussionmentioning
confidence: 59%
“…31,51,52 In addition, our study also found that personal health behavior and dietary characteristics influenced the imbalance of TCM body constitutions. 53–55 It was also worth noting that our study found that drug allergy, depression, somatic comorbidities, and nutritional characteristics of patients with IBS were significantly different from those of subjects with non-IBS in the Gentleness constitution. It was reasonable to speculate that the BCQ in TWB is a cumulative score calculation.…”
Section: Discussionmentioning
confidence: 59%
“…51 Regular exercise has negative correlations with the Yang-Xu, Yin-Xu, and stasis constitutions. 52,53 Baduanjin exercise modulates blood pressure, blood lipid metabolism, blood glucose, and oxidative stress. 9,10,54,55 Therefore, we postulated that 12-week Baduanjin exercise can modulate cardiovascular and metabolic parameters and then decrease the imbalanced TCM constitution.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted in 24 countries show consistent results that this instrument is valid. 11 The construct validity test uses factor analysis. The loading factor value was >0.5 and the eigenvalue values of the four domains >1 were valid.…”
Section: Methodsmentioning
confidence: 99%